Candidate High Redshift Clusters of Dusty Galaxies from Herschel and Planck. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Clements, D. L.; Greenslade, J.; ,
Abstract: By examining Herschel images in the HerMES & H-ATLAS surveys at the position of Planck Catalog of Compact Source sources we are able to determine the nature of the Planck sources. Most are simply nearby, known, dusty galaxies, while others are foreground galactic 'cirrus' dust. About 11% of sources, though, appear to be groups or clumps of fainter Herschel objects. Followup of a number of these indicates that they are galaxy clusters or protoclusters at z 1-3 that contain a number of galaxies undergoing contemporaneous massive starbursts. These sources present challenges for current galaxy & cluster formation/evolution models.